Acute Disseminated Encephalomyelitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The clinical and neuroradiological features of acute disseminated encephalomyelitis (ADEM) were determined by a retrospective review of medical records and MRI findings in 31 children (mean age 5.9 yrs; range 2-16 yrs) examined at the Royal Children's Hospital, Melbourne, Australia, between 1993 and 1998.